STAT3 signaling contributes to the high effector activities of interleukin‐15‐derived dendritic cells. Issue 5 (13th January 2015) - Okada, Starlyn; Han, Shuhong; Patel, Ekta S; Yang, Li‐Jun; Chang, Lung‐Ji
Abstract : Dendritic cells (DCs) are important innate and adaptive immune effectors, and have a key role in antigen presentation and T‐cell activation. Different lineages of DCs can be developed from hematopoietic progenitors following cytokine signaling, and the various lineages of DCs display distinct morphology, phenotype and functions. There has been limited information on differential cytokine‐mediated molecular signaling in DCs. Analyses of surface molecules by flow cytometry and quantitative RNA profiling revealed differences between DCs derived from interleukin‐4 (IL‐4) versus IL‐15 signaling, yet both lineages of DCs exhibited similar levels of surface molecules key to immune activation. Functional assays confirmed that IL‐15‐derived DCs elicited greater antigen‐specific, primary and secondary CD8 and CD4 T‐cell responses than did IL‐4‐derived DCs. Importantly, IL‐15 DCs secreted substantial amounts of proinflammatory cytokines, including IL‐6, interferon‐γ (IFN‐γ) and tumor necrosis factor‐α (TNFα), which helped polarize a strong T‐cell response. Assessment of signaling pathways revealed that IL‐15 DCs exhibited a lower levels of activated signal transducer and activator of transcription 5 (STAT5), STAT6 and extracellular signal‐regulated kinase 1/2 than IL‐4 DCs, but after lipopolysaccharide (LPS)/TNFα treatment, the STAT3 and p38 mitogen‐activated protein kinase (MAPK) activities were significantly enhanced in the IL‐15 DCs. Surprisingly, contrary to the canonical IL‐15‐mediated STAT5 signaling pathway in lymphoid cells, IL‐15 did not mediate a strong STAT5 or STAT3 activation in DCs. Further analysis using specific inhibitors to STAT3 and p38 MAPK pathways revealed that the STAT3 signaling, but not p38 MAPK signaling, contributed to IFN‐γ production in DCs. Therefore, while IL‐15 does not promote the STAT signaling in DCs, the increased STAT3 activity after LPS/TNFα treatment of the IL‐15 DCs has a key role in their high IFN‐γ effector activities.